COMPARISON OF AUTOMATIC STARRSED RS ERYTHROCYTE SEDIMENTATION RATE WITH MANUAL WESTERGREN METHOD - Ninik Sukartini; Siskawati Suparmin (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
This study aimed to compare the results of ESR measurements using Starrsed RS (30- and 60-minute mode) and manual Westergren method. We also investigate the effect of high leukocytes and haematocrit (Ht) on Starrsed RS ESR measurements. A cross-sectional study using K3EDTA anticoagulated blood samples from 140 subjects were conducted. A total of 21 samples with leukocytes count >50 000/µl were examined. The effect of Ht was studied using data from comparative study subjects.  The 60-minute mode Starrsed RS correlated very strongly [r = 0.98 (95%CI 0.97 to 0.98), p <0.0001], had good agreement [mean bias -0.4 mm (95%CI -1.46 to 0.74)], and gave no significant different results with manual Westergren method. The 30-minute mode Starrsed RS also has a very strong correlation [r = 0.97 (95%CI 0.96 to 0.98), p<0.0001] and good agreement [mean bias-2.9 mm (95%CI -4.23 to -1.58)], but has systematic difference with manual Westergren method. There was significant difference between manual method and Starrsed RS in samples with high leukocytes (p = 0.0208). There were no significant differences of ESR results measured by Starrsed RS dan manual Westergren method in the group of Htâ‰¤35% and >35%. The ESR on the Starrsed RS should still be read at 60 minute. Leukocytes>50 000/µl may affect ESR measurements on Starrsed but no effect of haematocrit was observed.